Who owns art? - The problem of trade in cultural objects - Piaskowska, Martyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the issue of trade in the scope of cultural objects. Presenting the selected topic the author focuses on the notion of cultural property, international instruments for protecting cultural goods and the Polish law system.